Surface-patterned chalcogenide glasses with high-aspect-ratio microstructures for long-wave infrared metalenses - Zhaofeng Gu; Yixiao Gao; Kongsi Zhou; Junyang Ge; Chen Xu; Lei Xu; Mohsen Rahmani; Ran Jiang; Yimin Chen; Zijun Liu; Chenjie Gu; Yaoguang Ma; et al. (Opto-Electronic Science)
Multidimensional-engineering chalcogenide glasses is widely explored to construct various infrared photonic devices, with their surface as a key dimension for wavefront control. Here, we demonstrate direct patterning high-aspect-ratio microstructures on the surface of chalcogenide glasses offers an efficient and robust method to manipulate longwave infrared radiations. Despite chalcogenide glass being considered soft in terms of its mechanical properties, we successfullyfabricate high-aspect-ratio micropillars with a height of 8 μm using optimized deep etching process, and we demonstrate a 2-mm-diameter all-chalcogenide metalens with a numerical aperture of 0.45 on the surface of a 1.5-mm-thick As2Se3 glass. Leveraging the exceptional longwave infrared (LWIR) transparency and moderate refractive index of As2Se3 glass, the all-chalcogenide metalens produces a focal spot size of ~1.39λ0 with a focusing efficiency of 47% at the wavelength of 9.78 μm, while also exhibiting high-resolution imaging capabilities. Our work provides a promising route to realize easy-to-fabricate, mass-producible planar infrared optics for compact, light-weight LWIR imaging systems.